Low-temperature conductive paste and raw material composition and preparation method thereof

By using surface-modified conductive metal powder and a suitable resin system, a low-temperature conductive paste with low resistivity and high adhesion is prepared, which solves the problem of insufficient conductivity and binding force in HBC batteries and improves the photoelectric conversion efficiency of the battery.

CN119724684APending Publication Date: 2025-03-28YOUYANNA MICRO NEW MATERIALS (BEIJING) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411893520.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Due to its special structure, HBC batteries have high performance requirements for low-temperature conductive paste, including better conductivity and binding force with transparent conductive oxide (TCO). The existing low-temperature conductive paste still needs to be improved.

Method used

A modified conductive metal powder containing hydroxyl, carboxyl and/or amide groups on the surface is prepared by combining thermosetting resins, latent curing agents, thixotropic agents and organic solvents to prepare low-resistivity low-temperature conductive paste to improve its adhesion and conductivity with TCO.

Benefits of technology

The low-temperature conductive paste has low resistivity and good adhesion after curing, which improves the photoelectric conversion efficiency of HBC batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724684A_ABST
    Figure CN119724684A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery slurry manufacturing, and particularly relates to low-temperature conductive slurry and a raw material composition and a preparation method thereof, and the raw material composition of the low-temperature conductive slurry comprises modified conductive metal powder, thermosetting resin, a latent curing agent, a thixotropic agent and an organic solvent, the surface of the modified conductive metal powder contains hydroxyl and carboxyl and / or acylamino. The raw material composition of the low-temperature conductive paste provided by the invention contains the modified conductive metal powder of which the surface contains hydroxyl and carboxyl and / or acylamino, so that the low-temperature conductive paste has low resistivity after being cured and has good adhesion with TCO, and the photoelectric conversion efficiency of an HBC battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery slurry manufacturing, and in particular to a low-temperature conductive slurry and a raw material composition and a preparation method thereof. Background Art

[0002] Heterojunction back-contact crystalline silicon cells (HBC) superimpose heterojunction cell (HJT) technology and interdigitated back-contact cell (IBC) technology. The theoretical limit efficiency reaches 29.1%, which is close to the upper limit of efficiency that crystalline silicon cells can achieve (29.4%), and has broad development prospects.

[0003] Low-temperature conductive paste is a key material for preparing HBC battery electrodes and plays a vital role in the photoelectric conversion efficiency of the battery. However, due to the particularity of its structure, HBC batteries have higher performance requirements for low-temperature conductive paste than ordinary HJT batteries. First, HBC batteries have eliminated the front grid lines. In order to achieve excellent photoelectric conversion efficiency, the paste-printed grid lines need to have better conductivity. Secondly, the back of the HBC cell changes from a 3μm to 5μm thick transparent conductive oxide (TCO) velvet surface to a 1μm to 2μm thick micro-velvet or polished surface, which makes it more difficult to technically ensure a good bonding force between the slurry and the cell.

[0004] Therefore, the existing low-temperature conductive slurry for HBC batteries still needs to be improved. Summary of the invention

[0005] The main purpose of the present invention is to propose a low-temperature conductive paste and its raw material composition and preparation method. The raw material composition of the low-temperature conductive paste provided by the present invention comprises a modified conductive metal powder having hydroxyl groups and carboxyl groups and / or amide groups on the surface, so that the low-temperature conductive paste has low resistivity after curing and has good adhesion to TCO, thereby improving the photoelectric conversion efficiency of the HBC battery.

[0006] The first aspect of the present invention provides a raw material composition for a low-temperature conductive paste, which comprises a modified conductive metal powder, a thermosetting resin, a latent curing agent, a thixotropic agent and an organic solvent, wherein the surface of the modified conductive metal powder contains hydroxyl groups and carboxyl groups and / or amide groups.

[0007] In some embodiments of the present invention, the modified conductive metal powder is obtained by surface-modifying the conductive metal powder using a solution containing a dispersant.

[0008] In some embodiments of the present invention, the conductive metal powder includes a first metal powder and a second metal powder, the first metal powder has a D50 particle size of 0.05 μm to 0.5 μm, and the second metal powder has a D50 particle size of 1.5 μm to 5 μm.

[0009] In some embodiments of the present invention, the mass ratio of the first metal powder to the second metal powder is 2:8 to 5:5.

[0010] In some embodiments of the present invention, the first metal powder includes one or more combinations of silver powder or copper powder.

[0011] In some embodiments of the present invention, the second metal powder includes one or more combinations of silver powder, copper powder, silver-coated copper powder, silver-coated aluminum powder, and nickel-coated copper powder.

[0012] In some embodiments of the present invention, the dispersant comprises one or more compounds having a structural formula satisfying formula (1) and / or formula (2).

[0013] Formula (1); Formula (2); wherein n is 1 to 3, and R is a carbon chain structure of 11 to 17 carbons.

[0014] In some embodiments of the present invention, the dispersant includes one or more combinations of 12-hydroxystearic acid, 12-hydroxystearic acid amide, 9,10-dihydroxystearic acid, 16-hydroxypalmitic acid, 9,10,16-trihydroxypalmitic acid, and 12-hydroxylauric acid.

[0015] In some embodiments of the present invention, based on the total mass of the raw material composition as 100%, the raw material composition includes the following components in mass percentage: 88% to 94% of modified conductive metal powder; 1.5% to 5% of thermosetting resin; 0.1% to 1% of latent curing agent; 0.02% to 0.1% of thixotropic agent; and the remainder of organic solvent.

[0016] In some embodiments of the present invention, the thermosetting resin includes one or more combinations of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, polyester resin, and acrylic resin.

[0017] In some embodiments of the present invention, the organic solvent includes one or more combinations of butyl carbitol, butyl carbitol acetate, and dibasic acid esters.

[0018] In some embodiments of the present invention, the latent curing agent includes one or more combinations of dicyandiamide, 2,4-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-methylbenzimidazole, and blocked isocyanate.

[0019] In some embodiments of the present invention, the thixotropic agent includes one or more combinations of modified hydrogenated castor oil and polyamide thixotropic agents.

[0020] The second aspect of the present invention provides a method for preparing the low-temperature conductive paste of the first aspect, the method comprising mixing modified conductive metal powder with other raw material compositions of the low-temperature conductive paste to prepare the low-temperature conductive paste.

[0021] In some embodiments of the present invention, the conductive metal powder is dissolved in a solution containing a dispersant, and dried to obtain the modified conductive metal powder.

[0022] In some embodiments of the present invention, the mass of the dispersant is 0.1% to 1% of the mass of the conductive metal powder.

[0023] In some embodiments of the present invention, the solution containing the dispersant includes an alcohol solvent, more preferably one or more combinations of anhydrous ethanol and ethyl acetate.

[0024] In some embodiments of the present invention, the conductive metal powder is dissolved in a solution containing a dispersant under ultrasonic and stirring conditions, and the ultrasonic and stirring time is 40 min to 60 min.

[0025] In some embodiments of the present invention, the drying process is carried out at a temperature of 60° C. to 80° C. and for a time of 2 h to 6 h.

[0026] The third aspect of the present invention provides a low-temperature conductive paste, which is prepared by the preparation method described in the second aspect.

[0027] Compared with the prior art, the present invention achieves the following technical effects:

[0028] 1) In the present invention, by using a conductive metal powder having a hydroxyl group and a carboxyl group and / or an amide group on the surface, it can be better combined with the cured resin, so that the slurry has better strength after curing, and can promote the contact between the carrier and the TCO surface, thereby improving the adhesion between the slurry and the TCO.

[0029] 2) In the present invention, by using conductive metal powders containing hydroxyl groups, carboxyl groups and / or amide groups on the surface, the metal powders can be better combined with each other during the curing process as the organic carrier shrinks and the resin solidifies, thereby improving the conductive performance.

[0030] 3) By using the dispersant of the present invention to have hydroxyl groups and carboxyl groups and / or amide groups on the surface of the metal powder, the organic carrier and the metal powder can have better compatibility, and the metal powder can be evenly dispersed in the slurry.

[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:

[0033] Figure 1 It is a printed pattern for volume resistivity testing in the present invention;

[0034] Figure 2 It is a printed pattern for contact resistivity testing in the present invention. DETAILED DESCRIPTION

[0035] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concept of the present invention.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0037] In the description of the embodiments of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0038] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0039] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0040] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0041] In order to provide a low-temperature conductive paste which has low resistivity after curing, has good adhesion to a transparent conductive oxide (TCO), and can improve the photoelectric conversion efficiency of an HBC cell, the present invention provides a raw material composition of a low-temperature conductive paste, the raw material composition of the low-temperature conductive paste comprising a modified conductive metal powder, a thermosetting resin and an organic solvent, wherein the surface of the modified conductive metal powder contains a hydroxyl group and a carboxyl group and / or an amide group.

[0042] In the embodiment of the present invention, the surface of the modified conductive metal powder has hydroxyl groups and carboxyl groups and / or amide groups, so that the low-temperature conductive paste has low resistivity after curing and has good adhesion with TCO.

[0043] In an embodiment of the present invention, the modified conductive metal powder is obtained by surface-modifying the conductive metal powder using a solution containing a dispersant.

[0044] In an embodiment of the present invention, the dispersant includes one or more compounds having a structural formula satisfying formula (1) and / or formula (2). The use of such a dispersant can improve the compatibility between the organic carrier and the metal powder, and the metal powder can be evenly dispersed in the slurry.

[0045] Formula (1); Formula (2); wherein n is 1 to 3, and R is a carbon chain structure of 11 to 17 carbons.

[0046] In an embodiment of the present invention, one end of the molecule of this type of dispersant contains -COOH or CONH2, which can form a good dynamic bonding effect with the surface of the metal powder, and disperse the metal powder by relying on the steric hindrance of the dispersant molecule; the -OH group contained at the other end can improve the compatibility of the resin, so that the metal powder can be better dispersed in the organic carrier.

[0047] In some embodiments of the present invention, the dispersant includes one or more combinations of 12-hydroxystearic acid, 12-hydroxystearic acid amide, 9,10-dihydroxystearic acid, 16-hydroxypalmitic acid, 9,10,16-trihydroxypalmitic acid, and 12-hydroxylauric acid.

[0048] In some embodiments of the present invention, the conductive metal powder includes a first metal powder and a second metal powder, wherein the D50 particle size of the first metal powder is 0.05 μm to 0.5 μm, and the D50 particle size of the second metal powder is 1.5 μm to 5 μm. Exemplarily, the D50 particle size of the first metal powder can be 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm or any value that meets the above range. The D50 particle size of the second metal powder can be one of 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm, 5μm or any value that meets the above range.

[0049] In some embodiments of the present invention, the mass ratio of the first metal powder to the second metal powder is 2:8 to 5:5. For example, the mass ratio of the first metal powder to the second metal powder can be one of 1:1, 1:2, 1:3, 1:4 or any value satisfying the above range.

[0050] In some embodiments of the present invention, the first metal powder includes one or more combinations of silver powder or copper powder.

[0051] In some embodiments of the present invention, the second metal powder includes one or more combinations of silver powder, copper powder, silver-coated copper powder, silver-coated aluminum powder, and nickel-coated copper powder.

[0052] In some embodiments of the present invention, based on the total mass of the raw material composition as 100%, the raw material composition of the low-temperature conductive paste includes the following components in mass percentage: 88% to 94% of modified conductive metal powder, 1.5% to 5% of thermosetting resin, 0.1% to 1% of latent curing agent, 0.02% to 0.1% of thixotropic agent, and balance organic solvent.

[0053] In an embodiment of the present invention, the mass percentage of the modified conductive metal powder provided by the present invention can be one of 88%, 89%, 90%, 91%, 92%, 93%, 94% or any value satisfying the above range.

[0054] In an embodiment of the present invention, the mass percentage of the thermosetting resin provided by the present invention can be one of 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or any value that meets the above range.

[0055] In some embodiments of the present invention, the thermosetting resin includes one or more combinations of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, polyester resin, and acrylic resin.

[0056] In some embodiments of the present invention, the organic solvent includes one or more combinations of butyl carbitol, butyl carbitol acetate, and dibasic acid ester (DBE).

[0057] In an embodiment of the present invention, the mass percentage of the latent curing agent provided by the present invention can be one of 0.1%, 0.15%, 0.2%, 0.23%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any value satisfying the above range.

[0058] In some embodiments of the present invention, the latent curing agent includes one or more combinations of dicyandiamide, 2,4-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-methylbenzimidazole, and blocked isocyanate.

[0059] In an embodiment of the present invention, the mass percentage of the thixotropic agent provided by the present invention can be one of 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or any value satisfying the above range to improve the printing performance of the slurry.

[0060] In some embodiments of the present invention, the thixotropic agent includes one or more combinations of modified hydrogenated castor oil and polyamide thixotropic agents, which can improve the printing performance of the slurry.

[0061] In an embodiment of the present invention, the raw material composition of the low-temperature conductive paste includes modified conductive metal powder, thermosetting resin, latent curing agent, thixotropic agent and organic solvent, and the surface of the modified conductive metal powder contains hydroxyl groups and carboxyl groups and / or amide groups.

[0062] The present invention also provides a method for preparing a low-temperature conductive paste. The key to preparing the low-temperature conductive paste is to mix the prepared modified conductive metal powder with other raw material compositions of the low-temperature conductive paste.

[0063] In the embodiment of the present invention, the thermosetting resin, latent curing agent, thixotropic agent and organic solvent are fully stirred and uniformly mixed, and the modified conductive metal powder is added, and the low-temperature conductive slurry is prepared by pre-stirring, grinding with a three-roll grinder and vacuuming. The slurry is prepared by the common preparation process of low-temperature slurry in the industry, which will not be described in detail.

[0064] In an embodiment of the present invention, the modified conductive metal powder is prepared by a solvent impregnation method, wherein the conductive metal powder is dissolved in a solution containing a dispersant, and the modified conductive metal powder is obtained after drying. The specific treatment process includes: immersing the conductive metal powder in a treatment solution containing a dispersant, and fully dispersing it under ultrasonic and stirring conditions for 40 minutes to 60 minutes, and then vacuum drying it at 60°C to 80°C for 2 hours to 6 hours to obtain a conductive metal powder modified by a dispersant, i.e., a modified conductive metal powder.

[0065] In an embodiment of the present invention, the conductive metal powder has a structure of or Modification of the dispersant can enhance its compatibility and dispersibility with the resin.

[0066] In an embodiment of the present invention, the mass of the dispersant is 0.1% to 1% of the mass of the conductive metal powder. For example, the mass of the dispersant can be one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% of the mass of the conductive metal powder or any value that satisfies the above range.

[0067] In an embodiment of the present invention, the solution containing the dispersant includes an alcohol solvent, wherein the alcohol solvent may be one or more combinations of anhydrous ethanol and ethyl acetate.

[0068] In an embodiment of the present invention, the conductive metal powder is dissolved in a solution containing a dispersant under ultrasound and stirring conditions, and the ultrasound and stirring time is 40 minutes to 60 minutes. Exemplarily, the ultrasound and stirring time can be one of 40 minutes, 42 minutes, 45 minutes, 48 ​​minutes, 50 minutes, 52 minutes, 55 minutes, 58 minutes, 60 minutes, or any value that satisfies the above range.

[0069] In an embodiment of the present invention, the temperature of the drying process is 60°C to 80°C, and the time is 2h to 6h. For example, the temperature of the drying process can be one of 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, or any value within the above range. The time of the drying process can be one of 2h, 3h, 4h, 5h, 6h, or any value within the above range.

[0070] The present invention also provides a low-temperature conductive paste, which is prepared by the above-mentioned preparation method. The low-temperature conductive paste of the present invention can meet the requirements of high conductivity and high adhesion of the grid line in the manufacture of HBC batteries.

[0071] The present invention also provides an HBC battery, which includes the above-mentioned low-temperature conductive slurry.

[0072] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0073] Example 1

[0074] A low-temperature conductive paste comprises the following raw materials in percentage by weight: 88% of modified conductive metal powder, 3% of bisphenol A epoxy resin, 1% of bisphenol F epoxy resin, 0.23% of 2,4-dimethylimidazole, 0.1% of modified hydrogenated castor oil, and 7.67% of butyl carbitol acetate.

[0075] The modified conductive metal powder is obtained by surface modifying the conductive metal powder using a solution containing a dispersant. The specific process is as follows:

[0076] The conductive metal powder includes silver powder with a particle size D50 of 0.1 μm and silver-coated copper powder with a particle size D50 of 2.5 μm, and the weight ratio of the silver powder to the silver-coated copper powder is 2:8.

[0077] The surface of silver powder with a particle size D50 of 0.1 μm was modified by immersing the silver powder in a first treatment liquid and fully dispersing it under ultrasonic and stirring conditions for 60 minutes, and then vacuum drying it at 60° C. for 4 hours to obtain modified silver powder. The first treatment liquid preparation method is as follows: 1% of the mass of the silver powder is weighed and dissolved in anhydrous ethanol 20 times the volume of the silver powder to obtain the first treatment liquid.

[0078] The surface of the silver-coated copper powder with a particle size D50 of 2.5 μm was modified by immersing the silver-coated copper powder in a second treatment liquid and fully dispersing it under ultrasonic and stirring conditions for 60 minutes, and then vacuum drying it at 70° C. for 4 hours to obtain the modified silver-coated copper powder. The second treatment liquid preparation method is as follows: 12-hydroxylauric acid with a mass of 0.2% of the mass of the silver-coated copper powder was weighed and dissolved in anhydrous ethanol with a volume of 20 times that of the silver-coated copper powder to obtain the second treatment liquid.

[0079] Preparation method of low-temperature conductive paste: Bisphenol A epoxy resin, bisphenol F epoxy resin, 2,4-dimethylimidazole, modified hydrogenated castor oil, and butyl carbitol acetate are fully mixed, and the above-mentioned modified silver powder and modified silver-coated copper powder are added, and low-temperature conductive paste 1 is obtained by pre-mixing, grinding with a three-roll grinder, and vacuuming.

[0080] Example 2

[0081] A low-temperature conductive paste comprises the following raw materials in percentage by weight: 94% of modified conductive metal powder, 2% of bisphenol F epoxy resin, 0.5% of bisphenol A epoxy resin, 0.15% of 2-ethyl-4-methylimidazole, 0.05% of modified hydrogenated castor oil, 1% of butyl carbitol, and 3.3% of DBE.

[0082] The modified conductive metal powder is obtained by surface modifying the conductive metal powder using a solution containing a dispersant. The specific process is as follows:

[0083] The conductive metal powder includes silver powder with a particle size D50 of 0.3 μm and nickel-coated copper powder with a particle size D50 of 3.5 μm, and the weight ratio of the silver powder to the nickel-coated copper powder is 3:7.

[0084] The surface of the silver powder with a particle size D50 of 0.3 μm was modified by immersing the silver powder in the third treatment liquid and fully dispersing it under ultrasonic and stirring conditions for 60 minutes, and then vacuum drying it at 80°C for 3 hours to obtain modified silver powder. The preparation method of the third treatment liquid is as follows: 9,10,16-trihydroxypalmitic acid with a mass of 0.7% of the mass of the silver powder was weighed and dissolved in anhydrous ethanol with a volume of 20 times that of the silver powder to obtain the third treatment liquid.

[0085] The nickel-coated copper powder with a particle size D50 of 3.5 μm was surface modified by immersing the nickel-coated copper powder in a fourth treatment liquid, fully dispersing the nickel-coated copper powder under ultrasonic and stirring conditions for 60 minutes, and then vacuum drying at 60° C. for 4 hours to obtain a modified nickel-coated copper powder. The fourth treatment liquid preparation method is as follows: 9,10,16-trihydroxypalmitic acid with a mass of 0.15% of the mass of the nickel-coated copper powder was weighed and dissolved in anhydrous ethanol with a volume of 20 times that of the nickel-coated copper powder to obtain a fourth treatment liquid.

[0086] Preparation method of low-temperature conductive paste: Bisphenol F epoxy resin, bisphenol A epoxy resin, 2-ethyl-4-methylimidazole, modified hydrogenated castor oil, butyl carbitol, and DBE are fully stirred, and the above-mentioned modified silver powder and modified nickel-coated copper powder are added, and low-temperature conductive paste 2 is obtained by pre-stirring, grinding with a three-roll grinder, and vacuuming.

[0087] Example 3

[0088] A low-temperature conductive paste comprises the following raw materials in percentage by weight: 93% of modified conductive metal powder, 1.5% of polyester resin, 0.1% of blocked isocyanate, 0.02% of polyamide and 5.38% of DBE.

[0089] The modified conductive metal powder is obtained by surface modifying the conductive metal powder using a solution containing a dispersant. The specific process is as follows:

[0090] The modified conductive metal powder includes silver powder with a particle size D50 of 0.42 μm and silver-coated copper powder with a particle size D50 of 5 μm, and the weight ratio of the silver powder to the silver-coated copper powder is 2:8.

[0091] The surface of the silver powder with a particle size D50 of 0.42 μm was modified by immersing the silver powder in the fifth treatment liquid and fully dispersing it under ultrasonic and stirring conditions for 40 minutes, and then vacuum drying it at 80° C. for 4 hours to obtain modified silver powder. The fifth treatment liquid preparation method is as follows: 12-hydroxystearic acid with a mass of 0.5% of the weight of the silver powder was weighed and dissolved in ethyl acetate with a volume of 20 times that of the silver powder to obtain the fifth treatment liquid.

[0092] The surface of the silver-coated copper powder with a particle size D50 of 5 μm is modified by immersing the silver-coated copper powder in the sixth treatment liquid, and fully dispersing it under ultrasonic and stirring conditions for 60 minutes, and then vacuum drying it at 60° C. for 4 hours to obtain the modified silver-coated copper powder. The sixth treatment liquid preparation method is as follows: 12-hydroxystearic acid with a mass of 0.1% of the weight of the silver-coated copper powder is weighed and dissolved in ethyl acetate with a volume of 20 times that of the silver-coated copper powder to obtain the sixth treatment liquid.

[0093] Preparation method of low-temperature conductive paste: polyester resin, blocked isocyanate, polyamide, and DBE are fully stirred, and the modified silver powder and modified silver-coated copper powder are added, and low-temperature conductive paste 3 is obtained by pre-stirring, grinding with a three-roll grinder, and vacuuming.

[0094] Example 4

[0095] A low-temperature conductive paste comprises the following raw materials in percentage by weight: 90% of modified conductive metal powder, 4% of hydrogenated bisphenol A epoxy resin, 1% of bisphenol F epoxy resin, 1% of 2-ethyl-4-methylimidazole, 0.06% of polyamide, and 3.94% of butyl carbitol acetate.

[0096] The modified conductive metal powder is obtained by surface modifying the conductive metal powder using a solution containing a dispersant. The specific process is as follows:

[0097] The conductive metal powder includes copper powder with a particle size D50 of 0.5 μm and copper powder with a particle size D50 of 1.5 μm, and the weight ratio of the former to the latter is 5:5.

[0098] The copper powder with a particle size D50 of 0.5 μm was surface modified by immersing the copper powder in the seventh treatment liquid and fully dispersing it under ultrasonic and stirring conditions for 50 minutes, and then vacuum drying it at 60° C. for 6 hours to obtain modified copper powder. The seventh treatment liquid preparation method is as follows: 12-hydroxystearic acid amide with a mass of 0.4% of the weight of the copper powder was weighed and dissolved in ethyl acetate with a volume of 20 times that of the copper powder to obtain the seventh treatment liquid.

[0099] The copper powder with a particle size D50 of 1.5 μm was surface modified by immersing the copper powder in the eighth treatment liquid and fully dispersing it under ultrasonic and stirring conditions for 60 minutes, and then vacuum drying it at 60° C. for 4 hours to obtain modified copper powder. The eighth treatment liquid preparation method is as follows: 12-hydroxystearic acid amide with a mass of 0.25% of the weight of the copper powder was weighed and dissolved in ethyl acetate with a volume of 20 times that of the copper powder to obtain the eighth treatment liquid.

[0100] Preparation method of low-temperature conductive paste: hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, 2-ethyl-4-methylimidazole, polyamide, and butyl carbitol acetate are fully stirred, and the above-mentioned modified copper powder is added, and low-temperature conductive paste 4 is obtained by pre-stirring, grinding with a three-roll grinder, and vacuuming.

[0101] Comparative Example 1

[0102] The remaining operations are the same as those in Example 1, except that unmodified conductive metal powder is used to prepare low-temperature conductive paste 5 in Comparative Example 1. The unmodified conductive metal powder includes silver powder with a particle size D50 of 0.1 μm and silver-coated copper powder with a particle size D50 of 2.5 μm, and the weight ratio of the silver powder to the silver-coated copper powder is 2:8.

[0103] Comparative Example 2

[0104] The remaining operations are the same as those in Example 2, except that unmodified conductive metal powder is used to prepare low-temperature conductive paste 6 in Comparative Example 2. The unmodified conductive metal powder includes silver powder with a particle size D50 of 0.3 μm and nickel-coated copper powder with a particle size D50 of 3.5 μm, and the weight ratio of silver powder to nickel-coated copper powder is 3:7.

[0105] Comparative Example 3

[0106] The remaining operations are the same as those in Example 3, except that unmodified conductive metal powder is used to prepare low-temperature conductive paste 7 in Comparative Example 3. The unmodified conductive metal powder includes silver powder with a particle size D50 of 0.42 μm and silver-coated copper powder with a particle size D50 of 5 μm, and the weight ratio of the silver powder to the silver-coated copper powder is 2:8.

[0107] Comparative Example 4

[0108] The remaining operations are the same as those in Example 4, except that unmodified conductive metal powder is used to prepare low-temperature conductive paste 8 in Comparative Example 4. The unmodified conductive metal powder includes copper powder with a particle size D50 of 0.5 μm and copper powder with a particle size D50 of 1.5 μm, and the weight ratio of the former to the latter is 5:5.

[0109] Performance Testing

[0110] The low-temperature conductive pastes 1-4 prepared in the examples and the low-temperature conductive pastes 5-8 prepared in the comparative examples were printed on a HBC solar blue film with a velvet pyramid of 1 μm to 3 μm through a printing screen with a specific pattern, and then cured at 190° C. for 10 minutes.

[0111] Volume resistivity: The screen printing pattern for testing volume resistivity is as follows Figure 1 By testing the resistance, length, width and height of the cured grid line and using the formula: Volume resistivity = resistance × width × height / length, the volume resistivity is calculated.

[0112] Contact resistivity: The screen printing pattern for testing contact resistivity is as follows Figure 2 As shown in Figure 2, the contact resistivity is obtained by testing and fitting using the TLM method (transmission line measurement method).

[0113] Welding pull-out force test: The tinned copper strip is welded to the surface of a PAD (a contact point on the grid line of the battery cell used to connect the welding strip) with a size of 1mm×1mm, and the test result is obtained by a tensile tester.

[0114] The test results are shown in Table 1.

[0115] Table 1 Summary of properties of low temperature conductive pastes obtained in Examples and Comparative Examples

[0116] Group Volume resistivity, μΩ·cm <![CDATA[Contact resistivity, mΩ·cm 2 > Welding pull-out force, N Example 1 4.5 0.5 3 Comparative Example 1 8.1 2.3 1.2 Example 2 11.5 1 1.5 Comparative Example 2 36.7 6 0.5 Example 3 5.2 1.2 2.5 Comparative Example 3 9.5 4.5 0.8 Example 4 7.6 2.5 1.8 Comparative Example 4 41.2 12 0.2

[0117] It can be seen from Table 1 that the low-temperature conductive paste prepared in the present invention has significantly improved performance in terms of electrical properties and welding pull-out force.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A raw material composition of a low-temperature conductive paste, characterized in that: The invention comprises modified conductive metal powder, thermosetting resin, latent curing agent, thixotropic agent and organic solvent. The surface of the modified conductive metal powder contains hydroxyl group, carboxyl group and / or amide group.

2. The raw material composition of the low-temperature conductive paste according to claim 1, characterized in that: The modified conductive metal powder is obtained by surface-modifying the conductive metal powder using a solution containing a dispersant; Preferably, the conductive metal powder comprises a first metal powder and a second metal powder, the D50 particle size of the first metal powder is 0.05 μm to 0.5 μm, and the D50 particle size of the second metal powder is 1.5 μm to 5 μm; Preferably, the mass ratio of the first metal powder to the second metal powder is 2:8 to 5:5; Preferably, the first metal powder comprises one or more combinations of silver powder or copper powder; Preferably, the second metal powder comprises one or more combinations of silver powder, copper powder, silver-coated copper powder, silver-coated aluminum powder, and nickel-coated copper powder.

3. The raw material composition of the low-temperature conductive paste according to claim 2, characterized in that: The dispersant comprises one or more compounds having a structural formula satisfying formula (1) and / or formula (2), Wherein, n is 1 to 3, and R is a carbon chain structure of 11 to 17 carbons; Preferably, the dispersant includes one or more combinations of 12-hydroxystearic acid, 12-hydroxystearic acid amide, 9,10-dihydroxystearic acid, 16-hydroxypalmitic acid, 9,10,16-trihydroxypalmitic acid, and 12-hydroxylauric acid.

4. The raw material composition of the low-temperature conductive paste according to claim 1, characterized in that: Taking the total mass of the raw material composition as 100%, the raw material composition includes the following components in mass percentage: Modified conductive metal powder 88% to 94%; Thermosetting resin 1.5% to 5%; Latent curing agent 0.1% to 1%; Thixotropic agent 0.02%~0.1%; Residue of organic solvent.

5. The raw material composition of low-temperature conductive paste according to claim 1, characterized in that: The thermosetting resin includes one or more combinations of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, polyester resin, and acrylic resin; Preferably, the organic solvent includes one or more combinations of butyl carbitol, butyl carbitol acetate, and dibasic acid esters.

6. The raw material composition of low-temperature conductive paste according to claim 1, characterized in that: The latent curing agent includes one or more combinations of dicyandiamide, 2,4-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-methylbenzimidazole, and blocked isocyanate; Preferably, the thixotropic agent includes one or more combinations of modified hydrogenated castor oil and polyamide thixotropic agents.

7. A method for preparing a low-temperature conductive paste, characterized in that: The preparation method comprises mixing modified conductive metal powder with other raw material compositions of low-temperature conductive paste to prepare the low-temperature conductive paste.

8. The preparation method according to claim 7, characterized in that: Dissolving the conductive metal powder in a solution containing a dispersant, and drying the solution to obtain the modified conductive metal powder; Preferably, the mass of the dispersant is 0.1% to 1% of the mass of the conductive metal powder; Preferably, the solution containing the dispersant includes an alcohol solvent, more preferably one or more combinations of anhydrous ethanol and ethyl acetate.

9. The preparation method according to claim 8, characterized in that: Dissolving the conductive metal powder in a solution containing a dispersant under ultrasonic and stirring conditions, wherein the ultrasonic and stirring time is 40 min to 60 min; Preferably, the drying process is carried out at a temperature of 60° C. to 80° C. and for a time of 2 h to 6 h.

10. A low-temperature conductive paste, characterized in that: The low-temperature conductive paste is prepared by the preparation method described in any one of claims 7 to 9.

Citation Information

Cited By

  • Conductive slurry and preparation method of antioxidant copper powder in conductive slurry

    CN120032941A